Filtragem ambiental e diversidade funcional em uma comunidade de floresta úmida - Gomes, Jose Leonardo dos Santos (2023)
The functional attributes of plants have contributed to a better understanding of the functionality of ecosystems. Environmental factors, in turn, act as filters influencing the way species are distributed, consequently directing functional diversity in communities. Orbital remote sensors can provide a way to monitor changes in functional diversity in an optimal and efficient way. Given these facts, the functional attributes of an area of the Altitude Brejo Forest were measured. It was analyzed whether the environmental factors (Altitude, Land Inclination, Openness of the Canopy, Distance from the Disturbed Landscape, Chemical and Physical Soil Components) would be acting as potential filters influencing the local functional diversity of plants. It was also tested whether the variation in the functional diversity of the plants in the studied area could be monitored by satellite. The field study was carried out in the Mata do Pau Ferro State Park, Paraíba, Northeast, Brazil. Functional diversity was calculated using a dendrogram-based index from eight functional vegetative attributes. Functional diversity was tested as a dependent variable for the following predictive environmental filters: fertility, soil chemistry and physics, canopy openness, altitude, slope and distance from the disturbed landscape. The models were tested from a Stepwise analysis and the best model was selected through the Akaike Criterion (AIC). Functional diversity varied significantly as a function of altitude (p<0.001), organic matter content (p<0.001), soil physical structure (p<0.001) and distance from the disturbed area (p<0.001). This study also demonstrated a potential for integration between satellite data and the spatial variation of functional diversity in band and B12 (p=-0.396) of sentinel-2. It was concluded that in the rainforest studied, local environmental variables associated with soil components and altitude acted as abiotic filters, directing the functional diversity of plants in this community.